2007
DOI: 10.1002/jemt.20543
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural study on the body surface of the acanthocephalan parasite Dentitruncus truttae in brown trout

Abstract: Scanning electron microscope (SEM) investigations on the holdfast elements, proboscis hooks, and trunk spines of Dentitruncus truttae (Acanthocephala, Palaeacanthocephala), an endoparasite of Salmo trutta (brown trout), provide more data about the surface of these taxonomic relevant structures. In both acanthocephalan sexes, the fully everted cylindrical proboscis possessed 18 longitudinal rows of hooks with 18 hooks per row (rarely 19-20). Hook length varied according to position on the proboscis; apical hook… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The apical hooks were the longest (40.0-52.0 μm), and the middle hooks were the shortest (31.7-36.6 μm). Numerous (Dezfuli et al 2008). In this study, P laevis had vertically arranged hooks which were approximately 40 μm in length, and they exited only on the proboscis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The apical hooks were the longest (40.0-52.0 μm), and the middle hooks were the shortest (31.7-36.6 μm). Numerous (Dezfuli et al 2008). In this study, P laevis had vertically arranged hooks which were approximately 40 μm in length, and they exited only on the proboscis.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, most of the acanthocephalan studies have been focused on taxonomic features and pathological changes observed by light microscope (Chaicharn and Bullock 1967;Hatai et al 1987;Roubal 1993;Dezfuli et al 2008). Recently, scanning electron microscopy (SEM) has been proven useful for studying the hook and tegument features of acanthocephalans and the morphology of alterations of the digestive tract (Wayland et al 2004;Alava and Aguirre 2005;Bayoumy et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The surface striations noted on the proboscis hooks have been previously reported in only 1 acanthocephalan species, Dentitruncus truttae Sinzar, 1955 (Palaeacanthocephala) by Dezfuli et al (2008). Trunk spines in both D. truttae and R. ornatus had unstriated smooth surfaces.…”
Section: Remarksmentioning
confidence: 59%
“…In addition to their present reporting in N. dimorphospinus (Eoacanthocephala: Neoechinorhynchidae), ribbed hooks have also been reported in 3 other species in 2 other families of Palaeacanthocephala: Dentitruncus truttae Sinzar, 1955 (Illiosentidae), Rhadinorhynchus ornatus Van Cleave, 1918 (Rhadinorhynchidae), and Leptorhynchoides polycristatus Amin, Heckmann, Halajian, El-Naggar, Tavakol, 2013 (Rhadinorhynchidae). Dezfuli et al (2008) and Amin et al (2009) suggested that such hook striations may provide a more effective attachment to the host's intestine. The striations of the hooks of D. truttae appeared as small dents on the outer periphery of the hooks' outer striped layer (Dezfuli et al, 2008).…”
Section: Resultsmentioning
confidence: 96%
“…Dezfuli et al (2008) and Amin et al (2009) suggested that such hook striations may provide a more effective attachment to the host's intestine. The striations of the hooks of D. truttae appeared as small dents on the outer periphery of the hooks' outer striped layer (Dezfuli et al, 2008).…”
Section: Resultsmentioning
confidence: 96%